SISTEM INFORMASI PENJUALAN BARANG BERBASIS WEB PADA TOKO SINAR HARAPAN MAKASSAR - Mashud Mashud; Askar; Herman (Universitas Sains dan Teknologi Komputer, 2020)
Sinar Harapan store which is engaged in construction materials has regular customers who are outside the area, so a sales information system is needed to help customers buy and receive product information from the store. This web-based information system can help shop customers shop online without having to visit the store in person. The purpose of this research is to design and implement a web-based merchandise sales system at the Sinar Harapan Makassar store. Data obtained through field research, library research and interviews. The system design uses PHP as a programming language and MySQL as the database storage. The information system for selling goods is based on the Sinar Harapan Makassar Store based on the results of the implementation test with the user acceptance test getting an average weight of 36 with a percentage of 90% so this application is very suitable for use